2016
DOI: 10.1186/s13018-016-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive plate osteosynthesis vs conventional fixation techniques for surgically treated humeral shaft fractures: a meta-analysis

Abstract: BackgroundIn this study, we performed a meta-analysis to identify whether minimally invasive plate osteosynthesis (MIPO) was superior to conventional fixation techniques (CFT) for treating humeral shaft fractures.MethodsA systematic literature search was conducted up to February 2016 in ScienceDirect, Springer, MEDLINE, and PubMed databases for relevant papers that compared the outcomes of MIPO with CFT, such as open reduction with plate osteosynthesis (ORPO) and intramedullary nail (IMN) for treating humeral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
1
23
1
4
Order By: Relevance
“…First, this study can be considered the first network meta-analysis of a randomized trial that evaluates the surgical procedures for humeral shaft fractures. Although several meta-analyses regarding this title have been published, [12, 13, 38] none are network meta-analyses. Second, a major strength of present study is that all of the included studies used a randomized controlled design, which increases the comparability between the two groups and reduces the probability of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study can be considered the first network meta-analysis of a randomized trial that evaluates the surgical procedures for humeral shaft fractures. Although several meta-analyses regarding this title have been published, [12, 13, 38] none are network meta-analyses. Second, a major strength of present study is that all of the included studies used a randomized controlled design, which increases the comparability between the two groups and reduces the probability of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Good clinical outcomes are generally achieved with intramedullary nailing as well as with plating. A recent meta-analysis showed an advantage for anterior Minimally Invasive Plate Osteosynthesis (MIPO technique with inserted 4.5 mm LCP) with regard to postoperative complications [31]. However, DP with a distal humeral plate and an additional reconstruction plate via a posterior approach can also achieve good clinical outcomes [32].…”
Section: Humeral Shaftmentioning
confidence: 99%
“…The minimally invasive technique has also found its place for its minor soft tissue injury during the procedure, 17 despite the concern regarding deformities resulting from an inadequate reduction of the fracture and safety for the radial nerve. 18 In the current study, similar non-consolidation rates were observed between the ORIF with plate and screws group and the bridge plating group (10.3% and 8.9%, respectively), which is in agreement with the literature findings.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In the current study, similar non-consolidation rates were observed between the ORIF with plate and screws group and the bridge plating group (10.3% and 8.9%, respectively), which is in agreement with the literature findings. 17 , 18 Both groups presented the same number (two) of patients with radial nerve praxia after the procedure that had not been identified on admission. In their meta-analysis, Hu et al 17 demonstrated a statistically significant difference in radial nerve injury after the procedure, higher in the group of conventional osteosynthesis with ORIF with plate and screws.…”
Section: Discussionmentioning
confidence: 99%